Morphometric and bioacoustic data on three species of Pseudopaludicola Miranda-Ribeiro, 1926 (Anura: Leptodactylidae: Leiuperinae) described from Chapada dos Guimarães, Mato Grosso, Brazil, with the revalidation of Pseudopaludicola ameghini (Cope, 1887) - Pansonato, André; Strüssmann, Christine; Mudrek, Jessica Rhaiza; Martins, Itamar Alves (Zootaxa, 2013)
Due to minute size, overall morphological similarities, scarcity of diagnostic characters after preservation, and usual sympatric or even syntopic occurrence of two or more species of Pseudopaludicola, the taxonomy of the genus is not yet a matter of consensus. Three species in the genus Pseudopaludicola Miranda-Ribeiro, 1926 were described by Cope in 1887, based on material obtained at Chapada dos Guimarães, mid-western state of Mato Grosso, Brazil. One of these species, Pseudopaludicola ameghini, was subsequently synonymized to P. mystacalis. In this paper we present morphological and bioacoustic evidences supporting a full specific status for the three sympatric species of Pseudopaludicola described from Chapada dos Guimarães, including Pseudopaludicola ameghini Cope, 1887.